The Reciprocal Relationship Between Gang Involvement and Victimization by Peers: Findings from the Pittsburgh Girls Study - Gilman, Amanda B. (Journal of developmental and life-course criminology, 2017)
While research has consistently shown a correlation between gang involvement and peer victimization, less is known about the direction of this relationship, especially among girls. The current study tests competing hypotheses to determine whether girls become gang involved following victimization, whether they experience peer victimization as result of gang involvement or whether reciprocal relationships exist.